Implementasi Permainan Tonnis di SD Negeri Se-Kecamatan Tugu Kota Semarang (Department of Physical Education, Sport, Health and Recreation, 2016)
The purpose of this study was to determine how the implementation tennis game in the elementary school throughout Tugu sub-subdistrict of Semarang City in 2015 and its inhibiting and supporting factors. The research method used was the survey method while the methods of collecting data were observation, interviews and research documentation. The research instrument was interview questions addressed to the Head Master, Penjasorkes Teacher and student observation.Results from this study showed that the implementation of learning tennis game runs well seen from the results of interviews with the Head Master and Penjasorkes Teacher in the Elementary Schoool throughout the Tugu Sub subdistrict of Semarang City, 2015. Based on the results and discussion, it can be concluded that the implementation Tennis game in elementary school throughout the Tugu Subdistrict of Semarang City 2015 as a whole included in the good category.